Pengaruh Kualitas Layanan, Kemudahan Pengguna Serta Kepercayaan Pelanggan terhadap Minat Pengguna Pada Aplikasi BliBli.com - Yuni Astuti, Dwi; Zahra Aliyanti, Dila; Sulaiman, Nofita (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Blibli.com is an e-commerce site with an e-commerce concept which was founded on July 25 2011 by PT Global Digital Niaga (GDN). Looking at the current phenomenon, Blibli.com has five million downloads with a rating of 4.1 but only has 127,199 users. This research uses the variables Service Quality, User Ease, Customer Trust and User Interest. The purpose of this research is to determine the quality of service on user interest carried out by Blibli.com, determine the ease of use by Blibli.com customers, and determine customer trust in the influence of user interest variables.The population in this research is Blibli.com customers with a total sample of 181 respondents using a non-probability sampling method, namely purposive sampling technique. This research uses descriptive analysis techniques and simple regression. The results of this research show that the service quality, ease of use and customer trust in user interest in Blibli.com are